Nanobiosensors for monitoring of stem-cell differentiation and organoids - Son, Young Hoon; Jeong, Gun-Jae (Frontiers in Nanotechnology, 2025)
Nanobiosensors now allow continuous, nondestructive tracking of stem cell differentiation and organoid maturation. Classical assays such as immunostaining and polymerase chain reaction are invasive snapshots that overlook fast molecular events guiding lineage choice. Nanoscale probes operate inside living constructs, translating genetic, metabolic, and mechanical signals into optical, electrical, or magnetic readouts while leaving viability intact. This review arranges recent progress by cell type. In pluripotent systems CRISPR Cas13a fluorescence resonance energy transfer beacons, single layer molybdenum disulfide nanopores, and dCas9 SunTag reporters reveal minute scale waves of microRNA and transcription factor activity, addressing teratoma risk. Mesenchymal stromal cells use locked nucleic acid beacons, piezoelectric scaffolds, and magnetic tracers to quantify Notch signaling, mechano sensing, and engraftment. Brain, cardiac, and vascular organoids adopt microneedle electrode arrays, stretchable optical membranes, and impedance chips to monitor deep electrophysiology, contractility, and barrier integrity, while quantum dots and metal organic frameworks combine delivery and sensing across other organoid models. Key hurdles remain, including lack of fabrication standards, uncertain probe occupancy limits, and unclear regulatory pathways. Multimodal chips, artificial intelligence driven analytics, and biodegradable sensor substrates offer potential solutions, moving nanobiosensors closer to routine clinical use.